A simple correlation to estimate the resolution of concentric cylindrical DMAs for diffusive particles. (January 2023) - Carsí, M.; Alonso, M.
Abstract: Transfer functions of concentric cylindrical differential mobility analyzers (DMA) have been determined from MonteCarlo simulation of particles trajectories. 1250 simulation runs were performed for random values (within prescribed ranges) of particle size, DMA dimensions and flow rates. The DMA resolution obtained from simulations has proven to agree fairly well with that calculated from Stolzenburg's analytical transfer function for diffusive particles. Stolzenburg's model, however, is relatively intricate and does not permit to have a clear picture of how the involved variables affect resolution. Besides, under somehow extreme conditions Stolzenburg's transfer function deviate considerably from the MonteCarlo simulated curve. A simple equation is proposed to correlate resolution with the two dimensionless parameters used in former works: the aerosol-to-sheath flow rate ratio, and the ratio of electrostatic to thermal energy. The proposed correlation, valid for a DMA operating under balanced flow condition, agrees with the simulation results within a ±10% error. Highlights: Resolving power of 1250 DMAs obtained by MonteCarlo simulation. Resolution correlated with two dimensionless numbers: eV/kT and Qa/Qsh. Correlation agrees with MonteCarlo simulation within 10% error.